1996
DOI: 10.1093/qjmed/89.2.151
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variation in the referral of patients with chronic end stage renal failure for renal replacement therapy

Abstract: The number of dialysis units per million population is low in the UK by comparison with other European countries, and this may affect the referral of patients for renal replacement therapy. We used a Poisson regression model to analyse the spatial distribution of all 539 adult patients resident in south-west Wales (Dyfed and West Glamorgan) who started chronic renal replacement therapy between April 1985 and March 1994. Controlling for patient age, population distribution, socio-economic variables and ethnic g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 9 publications
1
25
0
Order By: Relevance
“…A great deal of work has been done in previous years to highlight the inequalities in RRT provision in the UK including the contribution of referral patterns -referral rates have been shown to be affected by both the geographical distance from a renal centre [7][8][9][10][11] and the level of resource available for RRT treatment [12]. Despite many recent advances in the provision of renal services in the UK and the now comparable rate of RRT incidence to that in most other Northern European countries [13], non-referral remained a concern amongst the consensus group.…”
Section: Discussionmentioning
confidence: 99%
“…A great deal of work has been done in previous years to highlight the inequalities in RRT provision in the UK including the contribution of referral patterns -referral rates have been shown to be affected by both the geographical distance from a renal centre [7][8][9][10][11] and the level of resource available for RRT treatment [12]. Despite many recent advances in the provision of renal services in the UK and the now comparable rate of RRT incidence to that in most other Northern European countries [13], non-referral remained a concern amongst the consensus group.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that there is an inverse relation of initiation of renal replacement therapy with distance (Roderick et al, 1999) and that referral of patients with ESRD, aged 60 years and over, decrease with distance to the treatment center (Boyle et al, 1996). This fact was confirmed by another study which found that the prevalence of renal replacement therapy fell significantly with longer travel times for dialysis, even when patients lived relatively close to a facility (White et al, 2006).…”
Section: Introductionmentioning
confidence: 84%
“…A recent study demonstrated that dialysis patients living farther from a renal unit had a lower likelihood of being referred for pre-ESRD nephrology care. 35 Previous studies have also reported poorer performance on dialysis quality measures, including timing of referral to nephrology care in areas with poor socioeconomic status. For example, Australian patients living in urban areas with higher socioeconomic deprivation scores were more likely to be referred late for nephrology care than other patients.…”
Section: Discussionmentioning
confidence: 99%